. Prognostic value of serum IL-2, IFN-γ, TNF-α, IL-6, and IL-8, IL-10 in elderly Patients underwent Thoracotomy : Prognostic value of serum IL-2, IFN-γ, TNF-α, IL-6, and IL-8, IL-10 - Chen, Jia; Meng, Lifeng (Journal of Medical Biochemistry, 2025)
Objective: To investigate the effect of different fluid therapy on TH1 and TH2 cytokines  ( IL-2, IFN-γ, TNF-α, IL-6, and IL-8 ,  IL-10 ) during perioperative period of thoracotomy in elderly patients. Methods:A total of 60 elderly patients who underwent thoracotomy from January 2022 to April 2024 were divided into the control group (CG) and the observation group (OG), with 30 cases in each group. The CG received routine fluid management, while the OG received goal-directed fluid management. The postoperative recovery status, fluid intake and output, hemodynamic indexes, TH1 and TH2 cytokine levels were compared between both groups. Results: The postoperative extubation time, drainage time, ICU stayand hospitalization time in the OG were reduced than those in the CG (P
Keywords: IL-2, IFN-γ, TNF-α, IL-6, and IL-8 , IL-10,Thoracotomy; Elderly; Inflammatory cytokines; Goal orientation; Fluid management